Arco Cupcakes / Zaidatul Zanariah Abdul Razak - Abdul Razak, Zaidatul Zanariah; Bolhasan Alumi, Nur Hazelea Sharleen; Buyong, Sulaiman (UITM Sarawak, Kampus Samarahan, 2012)
Arco Cupcakes is a partnership company which is wholly owned by a Bumiputera. There are criteria and conditions that have to be fulfilled which required involvement of effort and precision of producing our products. With such conditions, the business can run smoothly and organization goal can be achieved.Along with the cooperation among the executive in this company, we have planned firmly the operation from the administrative till the financial plan in order to equip our company performs with minimum barriers and greater returns. Administration Executive will supervise a unit or section that provides various types of administration support and operating department provides administration of a specific function or program within administrative support department. This person also supervises the staff performance and ensuring the staffs are trained with the purpose to utilize the resources effectively and efficiently.